Implementasi Permainan Tradisional Ular Naga Dalam Mengembangkan Sikap Prososial Pada Anak Usia 5-6 Tahun - Haerunnisah; Muslim; Hermansyah (Kilau Publishing, 2025)
The development of prosocial attitudes in early childhood is an important aspect in the formation of individual characters who care about others and their environment. The lack of activities that can foster prosocial values is often a challenge in early childhood education institutions. This study aims to examine the implementation of traditional games of the Dragon Snake in developing prosocial attitudes in children aged 5-6 years. This research uses descriptive qualitative methods with the main data sources of students, teachers and related documents at Kuncup Muda Kindergarten. Data collection techniques include observation, interviews, and documentation, while data analysis is carried out through the steps of data reduction, data presentation, and conclusion drawing. The results showed that the implementation of the traditional game Snake Dragon in Kuncup Muda Kindergarten involved several stages, namely the introduction and understanding of the game, the formation of cooperation in groups, teaching the value of sharing and taking turns, developing children's communication skills, managing conflicts in groups, cultivating empathy and caring, as well as evaluation and reflection on the implementation of the game. This activity is effective in encouraging children to interact positively, understand other people's perspectives, and strengthen social relationships. The recommendation from this study is that teachers in early childhood education more often utilize traditional games such as the Dragon Snake as an interactive and fun learning medium to support the development of children's prosocial attitudes.